The Harmonizing Perspective of Theoretically Theological (Aqidah)-Based and Realistically Fiqhi-Based in Dealing with Pandemics and Plagues - Bichi, Mohammed Abdelhalim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
This research discusses the issue of pandemics in relation to the perceptions and views of Muslim theologians on the issues of evil and agony. Besides, it discusses the cause-effect relationship between infection and pandemics. It investigates how affliction affects humans as short and long-term chastisement as argued by the Mu’tazila, Asha’irah and Sufis on one hand and other Muslim philosophers on the other. The study discusses how such pandemics are addressed by Muslim scholars’ jurisprudential interpretations in line with worship, financial and urban countermeasures. It also discusses some essential medical and spiritual approaches to be used as preventative countermeasures against pandemics. The study concludes that it is “faith” that motivates humans to be patient and that instills in them essential values and principles for happiness and self-satisfaction.